TRADISI LAMPU COLOK DIDESA LUBUK MUDA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Sari, Rika Purnama; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Lubuk Muda village society has a tradition is lampu colok. Before presene its society electric use lampu colok lighting. This tradition begins from malay society wish to give lighting at month of Ramadhan. This tradition implement have clung heart by is society. While is month of Ramadhan they prepare things lampu colok. While arrive Ramadhan society prepare this lampu colok, this tradition done a year once. While comes Ramadhan society assembles lampu colok was looked around by house them. Precending society so viscous with mythâs those are trusted that on month of Ramadhan spiritâs will go home to house lampu colok as lighting the way that spirit. To analise research data is done with qualitative method and interpretation subject take purposive sampling. Subject consisting of society figure, religion figure, LAMâS chairman, chairman and member lampu colok and lubuk muda society. gathered and then explained by descriptive with is result of narasi is logical and analise use theory tindakan sosial and AGILâS theory. This research is Lubuk Muda village Siak Kecil district Bengkalis regency. Research at field indicate that there are two phases in realization lampu colok. Begining of look for tool and equipment until found gate and make design and tall in lampu colok. This research also after presene value in tradition lampu colok amongst those: solidarity value, morality value, art and economy value. Besides in tradition lampu colok also have function whic is: tightening frienship, increasing collaboration and enlivens Ramadhan ambience.Keywords: Tradition Lampu Colok, Village Lubuk Muda